A Study on Port Service Quality, Customer Satisfaction, Customer Loyalty, and Referral Intention: Focusing on Korean Container Terminals Amid Smart Port Development - Lele Zhou; Woojong Suh (Systems)
The evaluation of port service quality (PSQ) is critical for enhancing the competitiveness of container terminals. As technological innovation continues to reshape port operations, PSQ has shifted beyond operational efficiency to deliver smart, reliable, and sustainable services. However, few studies have addressed PSQ in the context of smart port evolution, especially with a focus on container terminals. This study employs a five-dimensional framework, comprising resources, outcomes, process, management, image, and social responsibility, to analyze how PSQ influences customer satisfaction and how customer satisfaction, in turn, affects customer loyalty and referral intention. The data was collected through a survey targeting users of container terminals in five major ports in Korea that undergoing smart port transformation, resulting in a final sample of 324 respondents. The findings reveal that resource-related, process-related, and image- & social responsibility-related PSQ dimensions significantly enhance customer satisfaction, which in turn has a positive effect on customer loyalty and referral intention. In contrast, the outcome-related and management-related dimensions did not have a significant impact on customer satisfaction. The analysis results and various implications discussed in this study are expected to provide helpful information and insights for establishing strategies to enhance the competitiveness of smart ports in the future.